PENGARUH DESAIN INTERIOR, KUALITAS PRODUK, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN (Studi Kasus Dapoer Yuga Cafe And Resto Kayu Arang, Sukaraja) - Ade Tiara Yulinda; Merta Kusuma; Winda Susanti (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2021)
ABSTRACTThis study aimed to determine the effect of interior design, product quality, and service quality on customer satisfaction at Dapoer Yuga Cafe and Resto, in Km. 28, Kayu Arang, Sukaraja. This research was a causality study with a quantitative method approach. The population in this study were all of Dapoer Yuga Cafe and Resto customers. The sampling technique used accidental sampling techniques with a total sample of 96 respondents. Data collection techniques used observation, interviews, and questionnaires with an instrument of validity and reliability. The data analysis techniques of this study were used descriptive statistical analysis, classic  assumption test, multiple linear regression analysis, coefficient of determination (R2), and hypothesis testing (t test and F test). The results of the study show that: (1) Interior design has a positive no significant effect on customer satisfaction, as evidenced by the value of t count of 1.256; significance value 0.212 ≥ 0.05; and the regression coefficient of 0.105; (2) Product quality has a positive and significant effect on customer satisfaction, evidenced by the value of t count of 3.077; significance value 0.003 ≤ 0.05; and the regression coefficient of 0.319; (3) Service quality has a positive and significant effect on customer satisfaction, as evidenced by the t count of 4.505; significance value 0.000 ≤ 5 0.05; and the regression coefficient of 0.316; (4) Interior design, product quality, and service quality simultaneously have a positive and significant effect on customer satisfaction, as evidenced by the F count of 49,691 with a significance of 0.000 ≤ 5 0.05; (5) The magnitude of the influence of interior design, product quality, and service quality on customer satisfaction (R2) is 61.8%.Keywords: Interior Design, Product Quality, Service Quality, Customer Satisfaction